Electroencephalography signal processing - Hui, Sheldon. (2009)
Victims of accidents are often permanently disabled due to nerve damage or loss of limbs. One solution to assist the paralyzed or “locked-in” patients is to implement automated assisted motion through Brain-Computer Interface (BCI) technology. To date, however, BCI is still in developmental stages due to difficulties of interpreting actual patient requests. Some of the most successful attempts at implementing BCI exercised the use of Steady State Evoked Potentials (SSVEPs) to translate human thoughts into palpable commands for control purpose